2020
DOI: 10.1038/s41598-020-67349-z
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated lipid nanocarrier for enhancing photodynamic therapy of skin carcinoma using curcumin: in-vitro/in-vivo studies and histopathological examination

Abstract: The use of (PEG)-grafted materials has a positive impact on drug delivery. In this study we designed PEGylated lipid nanocarriers (PLN) loaded with curcumin (Cur) to target skin cancer by photodynamic therapy. Cur is a polyphenolic compound having vast biological effects masked due to its low aqueous solubility. PLN were prepared using Tefose 1500 with different surfactants. PLN3, containing Tween 80, had the smallest particle size (167.60 ± 15.12 nm), Z = − 26.91 mV and, attained the highest drug release (Q24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…Abdel Fadeel et al demonstrated the beneficial effects of PDT with violet light (410 nm) and Cur-loaded PEGylated lipid nanoparticles in an in vitro study with increased cytotoxicity in cell culture, human squamous cell carcinoma cell line (A431), and in vivo skin carcinoma in mice [146].…”
Section: Skin Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Abdel Fadeel et al demonstrated the beneficial effects of PDT with violet light (410 nm) and Cur-loaded PEGylated lipid nanoparticles in an in vitro study with increased cytotoxicity in cell culture, human squamous cell carcinoma cell line (A431), and in vivo skin carcinoma in mice [146].…”
Section: Skin Cancermentioning
confidence: 99%
“…Table 2 highlights some of the effects of PDT and curcumin nanoformulations in skin cancers, by significantly improving the bioavailability and stability of nanocurcumin, increasing cytotoxicity on malignant cells, but with low phototoxicity on normal keratinocytes, the apoptotic effects and molecular mechanisms by generating high levels of ROS, along with the significant depolarization of mitochondrial membranes, while other in vitro experiments on mice demonstrated significant cell migration in the denuded area and highlighted the modulatory role of nanocurcumin on excessive production and the accumulation of ROS generated by laser irradiation [145,146,155,159,160,162].…”
Section: Skin Cancermentioning
confidence: 99%
“…The photodynamic therapy (PDT) for the targeting of photosensitive drugs, such as 5-aminolevulinic acid (5-ALA), which is used to induce the production of protoporphyrin IX in cells [ 5 , 49 , 50 ], has also been exploited for the treatment of skin cancer. PDT is based on the use of a photochemical reaction between a light source of a specific wavelength and a photosensitizer in the presence of oxygen [ 51 ]. It is effective, safe, and has a long-term effect; however, because it has a hydrophilic precursor, it has a limited permeation through the skin.…”
Section: Hyperproliferative Skin Diseasesmentioning
confidence: 99%
“…The authors observed that when encapsulated in liposomes, 5-ALA increased the production of protoporphyrin in the skin. Fadeel et al proposed the use of polyethylene glycol-grafted (PEGylated) lipid nanocarriers loaded with curcumin to target skin cancer by photodynamic therapy [ 51 ]. Curcumin is an aromatic phytoextract obtained from the turmeric rhizome of Curcuma longa , with known anti-oxidant, anti-inflammatory and anti-cancer properties [ 53 ].…”
Section: Hyperproliferative Skin Diseasesmentioning
confidence: 99%
“…[ 7 ] In the treatment of malignant tumor, radiotherapy and biotherapy are mainly through inducing apoptosis to achieve therapeutic effect. [ 8 ] At present, the construction of clinical prediction models mainly focuses on MM and no researchers have constructed clinical prediction models for all kind of skin cancer to predict the prognosis of skin cancer. [ 9 ] So we used patient data collected from the Surveillance, Epidemiology, and End Results Program (SEER) database to construct and validate our model for clinical prediction of skin cancer, hoping to provide a reference for clinical treatment of skin cancer.…”
Section: Introductionmentioning
confidence: 99%